Clinical and functional staging of oral submucous fibrosis - S. M. Haider,* A. T. Merchant, F. F. Fikree, M. H. Rahbar (Blackwell Synergy, 2000)
Oral submucous fibrosis is an insidious, precancerous, chronic disease that may affect the entire oral cavity and sometimes extends to the pharynx.1,2 Although it is occasionally preceded by formation of vesicles, it is always associated with sub-epithelial inflammatory reaction that is followed by fibroelastic change of the lamina propria with epithelial atrophy.3 This leads to stiffness of the oral mucosa resulting in trismus and inability to eat.